2015
DOI: 10.1194/jlr.m056754
|View full text |Cite
|
Sign up to set email alerts
|

HDL from apoA1 transgenic mice expressing the 4WF isoform is resistant to oxidative loss of function

Abstract: High levels of high density lipoprotein-cholesterol (HDL-C) are associated with lower risk for cardiovascular disease in epidemiological studies ( 1 ). Although several mechanisms may play a role in HDL's protective effect, HDL and its major protein constituent, apoA1, are critical components of the reverse cholesterol transport (RCT) pathway, in which cholesterol is removed from peripheral tissues and transferred to the liver for excretion. In the fi rst step of the RCT pathway, lipid-poor apoA1 acts as an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…56 PIP2 carried on circulating HDL might also serve as a signaling molecule by the delivery of PIP2 to target cells via SR-BI. In wildtype mice we observed plasma PIP2 levels at ~0.4 μM; however, with plasma apoA1 of ~ 32 uM 57 , and assuming on average 2.5 apoA1 molecules per HDL, the final HDL concentration is ~13 μM. Thus, it appears that there is less than one PIP2 molecule per HDL particle in circulation.…”
Section: Discussionmentioning
confidence: 64%
“…56 PIP2 carried on circulating HDL might also serve as a signaling molecule by the delivery of PIP2 to target cells via SR-BI. In wildtype mice we observed plasma PIP2 levels at ~0.4 μM; however, with plasma apoA1 of ~ 32 uM 57 , and assuming on average 2.5 apoA1 molecules per HDL, the final HDL concentration is ~13 μM. Thus, it appears that there is less than one PIP2 molecule per HDL particle in circulation.…”
Section: Discussionmentioning
confidence: 64%
“…2 H 2 O labeling-based HDL turnover method also was applied to assess the effect of different isoforms of apoAI and gender on in vivo HDL function in wild-type human transgenic apoAI mice and mice with 4WF isoform of human apoAI, in which 4 tryptophan residues are substituted with phenylalanine [86]. The in vitro cholesterol efflux assay demonstrated that the 4WF isoform of apoAI was resistant to myeloperoxidase-induced loss of function while human apoA1 transgenic HDL lost all ABCA1-dependent cholesterol acceptor activity.…”
Section: Animal Studiesmentioning
confidence: 99%
“…In fact, the impact of MPO‐mediated oxidation on an apoA‐I variant in which all Tyr residues were conservatively replaced with Phe was equivalent to the impact on wild‐type apoA‐I (8). In contrast, an apoA‐I variant in which all 4 Trp were conservatively replaced with Phe (4WF‐ApoA‐I) was immune to MPO‐mediated impairment of the cholesterol acceptor function (9, 18, 19). This observation indicates that MPO‐mediated oxidation of Trp plays a central role in apoA‐I loss of function (9).…”
mentioning
confidence: 99%
“…In the case of ATP binding cassette transporter A1 (ABCA1)-mediated release of cellular cholesterol toward apoA-I, its extracellular recipient, the disagreement is even more pronounced (3,4,6,8,9,11,14,(16)(17)(18)(19). In vitro, chlorination levels of apoA-I Tyr residues tightly correlate with a reduction in cellular cholesterol release capacity (3,4,11) and in vivo, they correlate with the incidence of cardiovascular events and atherosclerosis (14,16,17).…”
mentioning
confidence: 99%